Making connections: reflection, feedback and support - Jane Seale (Association for Learning Technology, 2007)
Hansell (1974) conceptualized seven different connections or attachments that we have to the world in which we live: attachments that consist of connections to other people, to a social role as well as to a system of meaning. For many, learning is at the heart of the process of making connections, particularly meaningful connections (Horton, 2000). If this is true, then it leads us to consider the extent to which educators, the systems they work in and the tools they use have a role to play in helping learners make those meaningful connections. For example, Scherer (2002, p. 5) suggests that educational systems have a responsibility to: